Immersive learning research - Morgado, Leonel (2018)
Welcome to the Journal of Universal Computer Science (J.UCS) special issue organized by the Immersive Learning Research Network (iLRN) following the 2017 iLRN conference. This issue includes eight papers on the focused topic "Immersive Learning Research", including extended versions of papers presented at iLRN 2017 and articles from the public call for papers.